Statistical thermodynamics : fundamentals and applications - Laurendeau, Normand M., 1944- (New York : Cambridge University Press, 2005)
"Statistical Thermodynamics: Fundamentals and Applications discusses the fundamentals and applications of statistical thermodynamics for beginning graduate students in the engineering sciences. Building on the prototypical Maxwell-Boltzmann method and maintaining step-by-step development of the subject, this book makes few presumptions concerning students' previous exposure to statistics, quantum mechanics, or spectroscopy. The book begins with the essentials of statistical thermodynamics, pauses to recover needed knowledge from quantum mechanics and spectroscopy, and then moves on to applications involving ideal gases, the solid state, and radiation. A full introduction to kinetic theory is provided, including its applications to transport phenomena and chemical kinetics. A highlight of the textbook is its discussion of modern applications, such as laser-based diagnostics. The book concludes with a thorough presentation of the ensemble method, featuring its use for real gases"--
Each chapter is carefully written to address student difficulties in learning this challenging subject, which is fundamental to combustion, propulsion, transport phenomena, spectroscopic measurements, and nanotechnology. Students are made comfortable with their new knowledge by the inclusion of both example and prompted homework problems."--Jacket.
Includes bibliographical references (p. 439-441) and index.
Keywords: Whitman College -- Memorial bookplates -- Class of 1978.; Statistical thermodynamics; Statistische Thermodynamik